FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA DALAM MEMILIH PROGRAM STUDI PADA PERGURUAN TINGGI - MUKHTAR GALIB; Muhammad Hidayat (AkMen JURNAL ILMIAH, 2020)
This study was intended to determine the effect of attitudes, norms, control and interest in student decisions in choosing study programs at Higher Education, this study was conducted at STIMLASH JAYA Makassar by taking 69 students as research samples. The results of this study prove that partially proven if attitudes, norms and interests affect student decisions while control has no effect on student decisions. This study also proves simultaneously the attitudes, norms, controls and interests influence the student's decision in choosing a study program at Higher Education.